Analysis of track circuits work and automatic signaling on pass section with steep gradient - Razgonov, A. P.; Yaschuk, K. I. (Science and Transport Progress, 2011)
Functioning of the track circuits and automatic block system on a pass section with a steep profile has been investigated. The traction calculations, the thermal operating modes of choke transformers, the operating regimes of track circuits with installing two choke transformers on supply and relay ends have been determined.